OPTIMIZING HEATED AIR CIRCULATION IN SILO/BIN DESIGN: A PARAMETRIC APPROACH - Okorie, Uche Nelson; Oluka, Sylverster Ike (FUDMA Journal of Sciences, 2024)
Aeration is one of the most essential processes after harvest in guaranteeing food security since it is often employed for grain cooling while the physical qualities of the stored grains are sustained. Aiming to address issues of storage inefficiencies, the research reviewed “Optimization of Heated Air Circulation in Silo/Bin Design: A Parametric Approach.” The method adopted for the study was systematic review of journal articles, conference proceedings, books and other relevant materials. Furthermore, the main method used to find relevant publications for the study was keyword searches in electronic databases such as Research Gate, Web of Science, Google Scholar and Scopus. Hence, the study ascertained that at an optimal temperature range between 10 - 15°C, grain storage facilities can effectively mitigate the risks of moisture accumulation, insect infestation, and microbial growth. More so, the study revealed that the rate of airflow ranging from 0.05 to 0.1 m3 min-1 t-1 are usually utilized in tall steel bins and concrete silos containing small grains, again measurements ranges from 0.1 to 0.2 meter cubed per minute per tonne were suggested for horizontal storage for huge grains. However, the study suggests that SSR model seems to be the most suitable model for optimization of heated air circulation in silo/bin among all the reviewed models because it is capable of describing nearly all the systems’ dynamics.